Effect of mechanical stimulation on bone marrow stromal cell–seeded tendon slice constructs: A potential engineered tendon patch for rotator cuff repair. (May 2015) - Qin, Ting-Wu; Sun, Yu-Long; Thoreson, Andrew R.; Steinmann, Scott P.; Amadio, Peter C.; An, Kai-Nan; Zhao, Chunfeng
Abstract: Cell-based tissue engineered tendons have potential to improve clinical outcomes following rotator cuff repair, especially in large or massive rotator cuff tears, which pose a great clinical challenge. The aim of this study was to develop a method of constructing a functional engineered tendon patch for rotator cuff repair with cyclic mechanical stimulation. Decellularized tendon slices (DTSs) were seeded with BMSCs and subjected to cyclic stretching for 1, 3, or 7 days. The mechanical properties, morphologic characteristics and tendon-related gene expression of the constructs were investigated. Viable BMSCs were observed on the DTS after 7 days. BMSCs penetrated into the DTSs and formed dense cell sheets after 7 days of mechanical stretching. Gene expression of type I collagen, decorin, and tenomodulin significantly increased in cyclically stretched BMSC-DTS constructs compared with the unstrained control group ( P < 0.05). The ultimate tensile strength and stiffness of the cyclically stretched tendon constructs were similar to the unstrained control group ( P > 0.05). In conclusion, mechanical stimulation of BMSC-DTS constructs upregulated expression of tendon-related proteins, promoted cell tenogenic differentiation, facilitated cell infiltration and formation of cell sheets, and retained mechanical properties. The patch could be used as a graft to enhance the surgical repair of rotator cuff tears.